1990
DOI: 10.1111/j.1365-2621.1990.tb01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and nutritional quality of Indonesian dried‐salted mackerel (Rastrelliger kanagurta)

Abstract: Indonesian mackerel (Rastrelliger kanagurta) were sun dried or salted and sun dried and stored at 30°C for up to 20 weeks in air. During processing and storage polyunsaturated fatty acids oxidized to form thiobarbituric acid (TBA) reactive substances and fluorescent compounds. TBA values increased with increasing salt content (range 2.3-20.7%). Positive, highly significant correlations were found between the odour of the stored products and both fluorescent pigment production and the degree of browning. Amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 12 publications
4
7
0
2
Order By: Relevance
“…These results agree with previous research carried out on fatty fish species such as sardine (Takiguchi, 1989), mackerel (Maruf et al, 1990) and horse mackerel (Aubourg and Ugliano, 2002). Indeed, brine freezing treatment has also been shown to lead to a higher lipid oxidation development as a result of an NaCl content increase in mackerel and horse mackerel muscle (Aubourg and Gallardo, 2005).…”
Section: Lipid Oxidationsupporting
confidence: 92%
See 2 more Smart Citations
“…These results agree with previous research carried out on fatty fish species such as sardine (Takiguchi, 1989), mackerel (Maruf et al, 1990) and horse mackerel (Aubourg and Ugliano, 2002). Indeed, brine freezing treatment has also been shown to lead to a higher lipid oxidation development as a result of an NaCl content increase in mackerel and horse mackerel muscle (Aubourg and Gallardo, 2005).…”
Section: Lipid Oxidationsupporting
confidence: 92%
“…Present results concerning the interaction compound (or tertiary lipid oxidation compounds) study have shown an important lipid oxidation formation that can be attributed to the NaCl presence in fish muscle. Such fluorescence and browning development produced in cases where an increased NaCl content is observed agrees with previous research under different processing conditions (Maruf et al, 1990;Lubis and Buckle, 1990;Aubourg and Ugliano, 2002;Aubourg and Gallardo, 2005). In the meantime, a temperature increase has been reported to lead to a higher interaction compound formation (Pokorný, 1981; GRASAS Y ACEITES, 59 (4) …”
Section: Fatty Acid Analysis and Polyene Indexsupporting
confidence: 90%
See 1 more Smart Citation
“…Amino acid composition of raw catfish fillets was similar to the composition reported for other fish species (Ismail et al, 2004;Maruf et al, 2007). The amino acid composition of raw and cooked catfish are presented in Table 3 and Table 4 as g amino acid/ 100 g sample.…”
Section: Amino Acid Compositionsupporting
confidence: 50%
“…This technique is directly related to weather conditions and thus makes the results uncertain. The main problems attributed to dried salted fish are the variable but often low quality final product, its high salt content, insect infestation and microbial contamination which induce a rapid rate of deterioration during transport, distribution and storage (Maruf, Ledward, Neale, & Poulter, 1990). Zuggaramundi and Lupin (1980) established a model allowing to obtain general relationships for salting kinetics and process equilibrium.…”
Section: Introductionmentioning
confidence: 99%